Maternal Cigarette Smoke Exposure Exaggerates the Behavioral Defects and Neuronal Loss Caused by Hypoxic-Ischemic Brain Injury in Female Offspring - Huang, Taida; Huang, Xiaomin; Li, Hui; Qi, Junhua; Wang, Nan; Xu, Yi; Zeng, Yunxin; Xiao, Xuewen; Liu, Ruide; Chan, Yik Lung; Oliver, Brian G.; Yi, Chenju; et al. (Frontiers in Cellular Neuroscience, 2022)
Objective: Hypoxic-ischemic encephalopathy affects ~6 in 1,000 neonates, leading to significant neurological sequela (e.g. cognitive deficits and cerebral palsy). Maternal smoke exposure (SE) is one of the common causes of neurological disorders; however, female offspring seems to be less affected than males in our previous study. We also showed that maternal SE exaggerated neurological disorders caused by neonatal hypoxic-ischemic brain injury in adolescent male offspring. Here, we aimed to examine whether female littermates of these males are protected from such insult. Methods: BALB/c dams were exposed to cigarette smoke generated from 2 cigarettes twice daily for 6 weeks before mating, during gestation and lactation. To induce hypoxic-ischemic brain injury, half of the pups from each litter underwent left carotid artery occlusion, followed by exposure to 8% oxygen (92% nitrogen) at postnatal day (P) 10. Behavioral tests were performed at P40-45, and brain tissues were collected at P45. Results: Maternal SE worsened the deficits in short-term memory and motor function in females with hypoxic-ischemic injury; however, reduced anxiety due to injury was observed in the control offspring, but not the SE offspring. Both hypoxic-ischemic injury and maternal SE caused significant loss of neuronal cells and synaptic proteins, along with increased oxidative stress and inflammatory responses. Conclusions: Oxidative stress and inflammatory response due to maternal SE may be the mechanism of worsened neurological outcomes by hypoxic-ischemic brain injury in females, which was similar to their male littermates shown in our previous study.